4-Hydroxyisoleucine inhibits tumor growth by triggering endoplasmic reticulum stress and autophagy - Peng Li; Yonghui Yang; Lu Qiu; Guangming Wan; Baomei Yuan; Yahong Wu; Yanfeng Gao; Guodong Li (Elsevier, 2022)
4-Hydroxyisoleucine（4-HIL）is a non-protein amino acid that is able to reduce obesity and improve insulin sensitivity in mice, and recently emerged as a drug candidate against hypoglycemia. For the first time, we found that 4-HIL exhibits a potent anti-tumor activity in various cancer cell lines in vitro and in vivo. Most importantly, 4-HIL has no cytotoxic effect on normal or non-malignant cells. Proteomic data analysis revealed changes in endoplasmic reticulum stress（ERS）related protein and autophagy related protein. Western blot revealed that molecular components of the ERS pathway were activated, including phosphorylation of perk and EIF2a increased, while levels of GRP78 reduced, the cellular process of ERS potentially contributed to the activation of autophagy, Transmission electron microscopy revealed the formation of autophagic vesicles under 4-HIL treatment, and LC3B was increased. Meanwhile, activation of ERS inhibits intracellular protein synthesis rate, our results suggest that 4-HIL exhibits anti-tumor activity in various cancer cell lines by increasing ERS and triggering autophagy responses without causing damage to normal cells.